Efektivitas Metode Pemberian Tugas dalam Meningkatkan Kreativitas Anak pada Masa Pandemi di TK Meraih Bintang - Tati Kartini; Nazia Rizka Amalia; Septi Ramyanti (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
Creativity in children is indicated by independence, skills, and attitudes in solving problems faced by children. Related to the basic framework of the PAUD curriculum, it is revealed that the purpose of Kindergarten Education is to build and develop the potential for the spiritual, intellectual, emotional, and social intelligence of students during their golden period of growth in an educational and fun play environment. The purpose of this study was to increase the creativity of early childhood through the assignment method. In learning to increase children's creativity by taking steps to make teaching preparations according to the theme being taught, preparing tools and materials to be used in learning, providing specific explanations about the activities to be carried out, dividing tools and materials to be used in learning and observing children's work processes. individually or in groups, summarize the results of children's activities and assess the development of children's abilities. Of course, in the Covid-19 pandemic, it will affect how children learn, so educators need to increase the effectiveness of children's learning by using time as well as possible.